(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Alzheimer´s disease impairs cognition, emotion, behavior, function performance and the social-familiar vinculum of the old person. The objective of this article is to present interventions of neuropsychological rehabilitation (NR) and cognitive-behavioral therapy (CBT) for patients with this disease. The method is descriptive, with qualitative analyses of a case study. Evaluations used Neuropsychiatry Inventory, Disability Assessment for Dementia, Cornell Scale for Depression in Dementia, Geriatric Depression Scale -15 and Anxiety Inventory. The intervention was planned to have 6 months of NR, and 6 months of CBT. Patient’s performance during RN and CBT was discussed. Improvements of mood, behavior and family relationships were observed.